REFLETINDO SOBRE A RELAÇÃO PRÁTICA/TEORIA/PRÁTICA NO PROCESSO DE FORMAÇÃO DO PROFESSOR DE LÍNGUA ESTRANGEIRA - Avelar, Flávia Juliana de Sousa (Intercâmbio, 2010)
Foreign language teacher education process has been discussed among the professionals of the area, since there are courses which priorize the teaching of technique, diminishing the importance of issues related to the teaching practice itself. Some other courses still priorize theory and dedicate little time to subjects which are necessary to the teacher education process, what makes the dicotomy between theory and practice even deeper. More recently, there has been a tendency of change in teacher education courses which, trying to relate practice to theory, make this “new” approach in teacher education process be seen in practice. Focusing on such aspects, this study aims to raise relevant questions related to teacher education process and classroom practice.